A numerical investigation of the effect of fin inclination angle on the thermal energy storage performance of a phase change material in a rectangular latent heat thermal energy storage unit. (March 2022) - Kim, Se Hyun; Pandey, Sudhanshu; Park, Seong Hyun; Ha, Man Yeong
Highlights: Numerical investigation on the thermal energy storage performance of vertical LHTES according to the fin angles ( θ f ). The results reveal that both the heat transfer characteristics and the energy storage performance are affected significantly by variations in θ f . For θ f in the range − 30 ∘ ≤ θ f ≤ − 10 ∘, the energy storage performance can exceed that for the case of θ f = 0 ∘ . The case of θ f = − 20 ∘ shows the best performance among all the cases considered in the present study. Abstract: In a numerical investigation of the thermal energy storage performance of a latent heat thermal energy storage system with three angled fins, the enthalpy-porosity model was used to simulate the phase-change process. To analyze the effect of the angle of inclination of the fin ( θ f ) on the heat transfer characteristics and energy storage performance, a parametric study was performed in which θ f was varied over the range − 40 ∘ ≤ θ f ≤ 40 ∘ . The variation in energy storage performance according to fin angle is also analysed, in order to obtain an optimal fin angle for maximum energy storage performance for the geometric shape of interest. The results reveal that both the heat transfer characteristics and the energy storage performance are affected significantly by variations in θ f . For cases where the fins are angled downwards, the upward flow is hampered, and where the fins are angled upwards, natural convection is intensified prior to the onset of thermal stratification. During the final stage of the charging process, the quantity of the remaining solid phase change material in the lower region increases, which delays the melting time. In order to evaluate the energy storage performance, the melting time, the total stored energy, and the mean power were calculated. For θ f in the range − 30 ∘ ≤ θ f ≤ − 10 ∘, the energy storage performance can exceed that for the case of θ f = 0 ∘ . The case of θ f = − 20 ∘ shows the best thermal energy storage performance as the average power is up to 19.3% higher than that for the case of θ f = 0 ∘ among all cases considered in present study.